ʺFormation of speech culture as an integral sign of national consciousness of students of the "Local studies and tourism work" educational program in the Ukrainian language classes (for professional orientation)ʺ. - Chuіeshkova, O. (Problems of Engineer-Pedagogical Education, 2024)
The article deals with the speech culture as one of the main criteria for the professional suitability of any specialist. It is emphasized that students of the educational and professional program – future historians, consultants on history, travel, archaeologists, teachers – are required to have a high level of literary language. Such a sign of speech culture as correctness was analyzed, the most typical violations of language norms by applicants were considered, the ways to eliminate these errors during the study of the "Ukrainian language (for professional orientation)" discipline were proposed. Attention is focused on dictional and orthographic purity of speech, difficulties in the process of mastering the lexical richness of the Ukrainian language, its grammar, stylistics and orthography. It is emphasized that, in addition to academic work, the educational one is also important for the speech culture formation. It is noted that scientific and pedagogical workers of the humanitarian departments of higher education institutions should in every possible way involve students in the study of folklore, folk traditions, life and activities of outstanding personalities of science, technology and culture, using for this purpose the works of classics and modern Ukrainian writers. It is emphasized that at UEPA the teachers of the Local History and Tourism, Social and Humanities Department annually hold the Ukrainian language Olympiads, the first stage of the Petro Yatsik International Ukrainian Language Competition and Taras Shevchenko International Language and Literary Competition for Pupils and Students, events for the Day of the Ukrainian writing and language, etc. It was concluded that without deep knowledge of the language, in particular its phonetic system, lexical structure, grammatical structure and stylistic properties, a modern specialist in the field of local history and tourism work is not be able to perform complex professional tasks and be competitive in the labor market. Oral and written speech of applicants should be objective, convincing in content, logical, civilized, bright in form, and above all – correct.